COMPARISON OF THE EXACT AND ASYMPTOTIC SOLUTIONS TO THE PROBLEM OF OSCILLATORY FLOW OF A VISCOUS FLUID IN A CYLINDRICAL PIPE (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2025)
This article explores the problems of oscillatory flow of a viscous incompressible fluid in a cylindrical pipe with a given harmonic oscillation are solvedaverage velocity across the pipe cross-sectionThe transfer function and amplitude-phase frequency characteristics were determined. Using these functions, the influence of oscillation frequency on the ratio of shear stress to the cross-sectional average velocity was determined.  By comparing the exact solution of the problem with the asymptotic solution, new asymptotic formulas are proposed that are of great importance in the study of the oscillatory flow of a viscoelastic fluid in a cylindrical pipe.
Keywords: Viscous fluid; transfer function; oscillatory flow; asymptotic formula; pulsating flow; cylindrical pipe